Harmonizing work safety and health practices towards technician's productivity in the workplace: A modified theory of planned behaviour - Olabanji Taiwo Shodipe; Ifeanyi Benedict Ohanu (Cogent Business & Management, 2023)
Several technicians have been exposed to danger and varying degree of risk, exposed to diverse grades of occupational and health hazard, injuries and death which may arise from accidents. Several factors that cause these accidents range from inadequate experience, short job tenure, insufficient training, etc. Therefore, this study harmonizes safety and health practices at work towards technician's productivity in the workplace. A total of 1,080 registered technicians in workplaces in Lagos State, South-West region, Nigeria, were used as sample in this study. The samples were selected using purposive sampling technique. Exploratory and confirmatory factor analyses were used during the empirical analysis to achieve the model fits. The study shows that there is a significant influence of the health and safety practice constructs (job safety, coworker's safety, supervisor's safety and management of safety practices) on the construct of theory of planned behaviour (attitude, subjective norms, perceived behavioural control and intentions) to further enhance technician safety and health practices/safety behaviour. The result from the study indicates that school-based occupational safety and health education may contribute to future reduction in job-related injury, to ensure that safe and healthy work becomes important to the student experience.
Keywords: 650; accident; productivity; Safety and health practices; safety attitude; workplace safety